Microbiome analysis and biocontrol bacteria isolation from rhizosphere soils associated with different sugarcane root rot severity - Li, Xinyang; Liu, Yue; Wang, Ziting; Yang, Chenglong; Zhang, Runzhi; Luo, Yibao; Ma, Yuming; Deng, Yizhen (Frontiers in Bioengineering and Biotechnology, 2022)
To explore the causal pathogen and the correlated rhizosphere soil microecology of sugarcane root rot, we sampled the sugarcane root materials displaying different disease severity, and the corresponding rhizosphere soil, for systematic root phenotype and microbial population analyses. We found that with increased level of disease severity reflected by above-ground parts of sugarcane, the total root length, total root surface area and total volume were significantly reduced, accompanied with changes in the microbial population diversity and structure in rhizosphere soil. Fungal community richness was significantly lower in the rhizosphere soil samples from mildly diseased plant than that from either healthy plant, or severely diseased plant. Particularly, we noticed that a peculiar decrease of potential pathogenic fungi in rhizosphere soil, including genera Fusarium, Talaromyces and Neocosmospora, with increased level of disease severity. As for bacterial community, Firmicutes was found to be of the highest level, while Acidobacteria and Chloroflexi of the lowest level, in rhizosphere soil from healthy plant compared to that from diseased plant of different severity. FUNGuild prediction showed that the proportion of saprophytic fungi was higher in the rhizosphere soil of healthy plants, while the proportion of pathogenic fungi was higher in the rhizosphere soil of diseased plants. By co-occurrence network analysis we demonstrated the Bacillus and Burkholderia were in a strong interaction with Fusarium pathogen(s). Consistently, the biocontrol and/or growth-promoting bacteria isolated from the rhizosphere soil were mostly (6 out of 7) belonging to Bacillus and Burkholderia species. By confrontation culture and pot experiments, we verified the biocontrol and/or growth-promoting property of the isolated bacterial strains. Overall, we demonstrated a clear correlation between sugarcane root rot severity and rhizosphere soil microbiome composition and function, and identified several promising biocontrol bacteria strains with strong disease suppression effect and growth-promoting properties.